2005
DOI: 10.1007/s00246-004-0726-1
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up Assessment of the Collateral Circulation in Patients with Kawasaki Disease Who Underwent Dipyridamole Stress Technetium-99m Tetrofosmin Scintigraphy

Abstract: To assess the alteration of myocardial ischemic findings and the role of collateral vessels in patients with Kawasaki disease (KD), we used dipyridamole stress technetium-99m tetrofosmin (Tf) single photon emission computed tomography (SPECT). A comparison study of coronary angiography and dipyridamole stress (0.70 mg/kg) Tf-SPECT was repeated at least twice in 20 patients. The subjects included 7 patients with coronary stenosis, 1 with pre- and post-coronary artery bypass grafting (CABG) due to coronary steno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…By applying the 20‐segment perfusion score, 9 significant myocardial SPECT abnormalities (score ≥4) were found in five patients: two patients in group 1, and three patients in group 2 (Fig. 1, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…By applying the 20‐segment perfusion score, 9 significant myocardial SPECT abnormalities (score ≥4) were found in five patients: two patients in group 1, and three patients in group 2 (Fig. 1, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, severely stenotic or occlusive coronary arteries as a sequelae of KD develop collaterals in the chronic phase of KD, most of which develop sufficiently to prevent myocardial infarction 7. Therein, recanalization or collateral formation improves the perfusion to the distal myocardium of the occluded native coronary artery 8,12. Contrary to this, Tatara, et al13 reported that the development of collateral vessels cannot protect against myocardial ischemia and the degree of collaterals have no effect on myocardial imaging.…”
Section: Discussionmentioning
confidence: 99%
“…A regular myocardial stress test and CAG should be done in patients with coronary arterial complications associated with KD. Fukuda, et al12 proposed that unnecessary CAG could be postponed until the time at which ischemic findings change in the dipyridamole stress SPECT. With myocardial ischemia, there are no evidence-based guidelines for follow-up and evaluation of patients with coronary abnormalities after KD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Myocardial scintigraphy has shown improved sensitivity for the detection of myocardial ischemia and tissue damage and has become the noninvasive method of choice for the assessment of ischemia and prognosis in these patients. 3,4 However, obstructive coronary lesions secondary to giant aneurysms in Kawasaki disease are often proximal, and the presence of diffuse and balanced ischemia may lead to a false-negative scintigraphy. In our patient, dipyridamole first-pass perfusion CMR showed diffuse myocardial ische- …”
mentioning
confidence: 99%